12th Gawad CCP para sa alternatibong pelikula at video - Fuentebella, Rommel (Animo Repository, 1999)
In the 12th Gawad CCP para sa Alternatibong Pelikula at Video, Rommel Fuentebella, Joyzel Coronado and Jessie James Abastilla landed 3rd place for the short video feature category, Sumpa. The feature was a story of a boy who figured in a number of tragic events and decided to keep silent with the grim belief that speaking again would trigger the death curse struck on him.